Bedaquiline resistance in drug-resistant tuberculosis HIV co-infected patients. Issue 6 (4th June 2020) - Nimmo, Camus; Millard, James; Brien, Kayleen; Moodley, Sashen; van Dorp, Lucy; Lutchminarain, Keeren; Wolf, Allison; Grant, Alison D.; Balloux, Francois; Pym, Alexander S.; Padayatchi, Nesri; O'Donnell, Max
Global tuberculosis (TB) control is threatened by drug resistance, with over 500 000 cases resistant to first-line drugs in 2018 [1]. Bedaquiline is a highly effective TB drug and has improved drug-resistant TB (DR-TB) outcomes in trial and programmatic settings [2, 3]. The World Health Organization (WHO) recommends its inclusion in most DR-TB regimens [4] and it is under further evaluation in clinical trials. There have been several reports of clinical bedaquiline resistance [5–8]. Resistance-associated variants (RAVs) in clinical isolates identified to date are almost exclusively caused by Rv0678 mutations which can raise Mycobacterium tuberculosis minimum inhibitory concentrations (MICs) for bedaquiline and clofazimine [9]. Genetic mutations linked to bedaquiline resistance were found before starting treatment and acquired during treatment in patients with drug-resistant TB and HIV in KwaZulu-Natal, South Africa. Routine bedaquiline resistance testing needs to be accelerated. http://bit.ly/2vnL4VY